The Effect of Music on the Performances of Taekwondo Athletes - Gacar, Atalay (Lahore Medical & Dental Coll, 2021)
It was observed that music is a tool that allows athletes to be motivated by relieving the pressure on the athletes before the competition in the researches. Based on these thoughts, in our research; It is aimed to examine the level of effect of music in the performances of taekwondo athletes. Within the scope of our research, 1206 athletes who were selected by random method from athletes engaged in taekwondo sports in Turkey were reached. Due to the pandemic affecting the whole world, the process of transmitting and filling scales to athletes was carried out by online survey method conducted through www.onlineanketler.com. In our study, the Personal Information form consisting of 5 articles and the Effect of Music scale in Sports Practices consisting of 18 articles and 3 sub-dimensions which developed by Karayol and Turhan was used in order to determine the demographic information of the athletes. IBM SPSS 22 package program was used in the analysis of the data obtained. It was accepted that the data showed a normal distribution by looking at the skewness and kurtosis values of the scales. Independent samples t test was used for paired comparisons and One Way Anova analysis was used for multiple comparisons in the study. The error level in the study was taken as p < 0.05. It was determined that there was no statistically significant difference between the sub-dimension scores of the effect of music in sports practices and the sports year variable depending on the sports year variable of the athletes engaged in taekwondo sport in Turkey (p > 0.05). Statistically significant differences were found in terms of sub-dimension scores and general scores of the scale depending on gender, age, educational status and type of music being listened to (p<0.05). It was observed that the effect of music in sports practices was higher than the average, with a score of 4.05 for the effect of music, 3.93 for psychological resilience, 3.99 for the physical strength and performance sub-dimension, and 4.23 for the motivation sub-dimension in line with the findings of the study.
Keywords: Athlete; Taekwondo; Music; Performance